Immunomodulatory effect of baculovirus in chickens : how it modifies the immune response against infectious bursal disease virus - Chimeno Zoth, Silvina Andrea (2016)
Several reports have shown that baculoviruses (BVs) have strong adjuvant properties on the mammalian immune system. Recent studies of our group demonstrated the ability of BV to stimulate the innate immunity in chickens. In this investigation, we aimed to assess the potential antiviral effect of BV given both, before and after infectious bursal disease virus (IBDV). In the first case, specific pathogen free chickens were intravenously inoculated with 5 × 10(7) pfu of Autographa californica nuclear polyhedrosis virus and 3 h later were orally administered 2.5 × 10(5) egg infectious doses 50 of IBDV. In the second case, chickens received IBDV 3 h before BV inoculation. Five days later, chickens were bled and euthanized. RNA from the bursa was analyzed for cytokine production. Also, bursae were used for virus recovery, and processed for lymphocyte isolation. The results showed that the administration of BV 3 h after the inoculation with IBDV produced important changes in the effect that IBDV causes in the bursa. BV reduced the infiltration of T lymphocytes, decreased the expression pattern of IL-6 and IFN-γ and inhibited IBDV replication. The results herein presented demonstrate that this Lepidopteran virus shows antiviral activity in chickens under experimental conditions. Investigations under field conditions have to be done to probe this strategy as a valuable sanitary tool for the treatment and prevention of chicken diseases